(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The organization is changing the Human Resource Management procedures, because of the turbulent work environment. The strategies to attract and retain the employees are not efficient in Public Administration. The study aims to examine the moderator role of career satisfaction in the relationship between organizational career management practices and entrenchment of civil servants. Method: The research adopts a quantitative method, involving 105 civil servants. To test the H1 e H2 we performed Hierarchical Multiple Regression and to test H3 and the potential moderator role of career satisfaction we performed also the Multiple Hierarchical Regression. Results: The study support positively the H1 and H2 and partially the H3. However, the when the civil servants are satisfied in the career, the entrenchment tend to reduce because the organizational career management are corresponding to the employee’s career expectation. Conclusion: The career satisfaction is high, when organizational career management practices are efficient which reduce the entrenchment of civil servants.